Prognosis of Idiopathic Sudden Sensorineural Hearing Loss: The Nomogram Perspective. (January 2023) - Wu, Huadong; Wan, Wei; Jiang, Hongqun; Xiong, Yuanping
Objective: The aim of this study is to create a nomogram for accurately predicting the prognosis of idiopathic sudden sensorineural hearing loss (ISSNHL) and provide a reference for clinical treatment. Methods: Three hundred and twenty-three patients with ISSNHL were admitted from September 2014 to November 2020. The clinical data were retrospectively reviewed. Prognostic factors for ISSNHL were assessed based on univariate and multivariate logistic regression analysis and used to create a nomogram. Nomogram performance in terms of predictive and discriminatory ability was evaluated by calculating the concordance index (C-index) and generating calibration plots. Results: The overall hearing improvement rate was 41.4%, comprising complete recovery (13.3%), marked recovery (17.0%), and slight recovery (11.1%). Multivariate logistic regression analysis showed that age, symptoms of vertigo, interval between onset and treatment, low-density lipoprotein, and type of hearing loss were independent predictors of ISSNHL. A nomogram based on these 5 factors had a C index of 0.798 (95% confidence interval 0.750-0.845). Conclusions: Age, vertigo, interval between onset and treatment, low-density lipoprotein level, and type of hearing loss are closely associated with hearing recovery. The nomogram may enable prediction of the prognosis of ISSNHL and facilitate clinical decision-making.